Glycoproteins of Sendai virus are transmembrane proteins. - Lyles, D S (1979)
Radiolabeled Sendai viral envelope proteins were incorporated into human erythrocyte membranes by the process of fusion of the viral envelope with the erythrocyte membrane. Inside-out (IO) vesicles were prepared from the erythrocyte membranes containing viral proteins, and the presence of viral proteins was assessed by electrophoresis in sodium dodecyl sulfate/polyacrylamide gels. Proteolysis with trypsin, chymotrypsin, or Pronase, which digests only the external surface of the IO vesicles (the cytoplasmic surface of the erythrocyte membrane) revealed that the viral nucleocapsid and the nonglycosylated inner-envelope (M) proteins were present on the external surface. In addition, small segments of the viral envelope glycoproteins (HN and F1) were removed by these proteases, while the major portions of the glycoproteins were protected from digestion, indicating that in the erythrocyte membrane they are transmembrane proteins. Results of experiments carried out on right side-out membranes, unsealed membranes, and membranes containing attached virus that was unable to fuse indicated that the results obtained with IO membranes could not be accounted for by contamination with these membrane species. The identify of the proteolysis products was confirmed by peptide mapping. The selective exposure of the cytoplasmic surface, and hence the internal components of the virus, in IO vesicles makes this membrane system an attractive model for studying the interactions involved in virus maturation at host cell membranes.